Hydrodynamics of bubble column reactors at high gas velocity: experiments and computational fluid dynamics (CFD) Simulations - Rampure, Mohan R.; Kulkarni, Amol A.; Ranade, Vivek V. (Industrial & Engineering Chemistry Research, 2007)
This paper focuses on the modeling of flow and mixing in a bubble column reactor operated at high gas velocities (up to 0.40 m/s). A dual-tip conductivity probe was used to measure local void properties such as local time-averaged gas holdup, chord length distribution, bubble velocity distribution, and interfacial area. Chord length distribution was converted to bubble size distribution, using the backward transformation method. Liquid-phase mixing time measurements were conducted using a conductivity probe. A computational fluid dynamics (CFD) model was developed to simulate the unsteady gas-liquid flow in a bubble column using commercial code FLUENT 6.2. The time-averaged flow properties predicted by CFD simulations were compared with the experimental data. The role of unsteady flow structures in mixing was studied. The `' multiple snapshots `' approach was used to simulate the mixing time using CFD. The mixing times that were predicted for all superficial gas velocities compared favorably to the measured values. This study of the hydrodynamic behavior of a bubble column at higher gas velocity provides a basis for understanding and simulating solid suspension (or solid mixing) in slurry bubble column reactors.

Hysteresis in cloud heights during solid suspension in stirred tank reactor: experiments and CFD simulations - Sardeshpande, Madhavi V.; Juvekar, Vinay A.; Ranade, Vivek V. (Aiche Journal, 2010)
Solid suspension in stirred tank reactor is widely used in process industries for catalytic reactions, dissolution of solids, crystallization, and so on. Suspension quality is a key issue in design and operation of stirred reactor and its determination is not straight forward. Cloud height measurements of solid suspension provide a relatively simple way to quantify quality of suspension. In this work, experiments were carried out to quantify variation of cloud heights with impeller speed and particle characteristics. These measurements were carried out using visual observations, image analysis, and ultrasound velocity profiler techniques. The obtained data demonstrated the existence of hysteresis in cloud heights with respect to impeller speed. Apart from possible applications in reducing power required for achieving desired solid suspension quality, the existence of hysteresis also provides a new way to evaluate computational fluid dynamics (CFD) simulations of solid liquid flows in stirred vessels. An attempt was made to capture observed hysteresis in cloud heights in CFD simulations. The simulated results were compared with the experimental data. The presented models and results (experimental and computational) will he useful for simulating complex solid liquid flows in stirred reactors. (C) 2010 American Institute of Chemical Engineers AIChE J, 56: 2795-2804, 2010
Keywords: CFD; hysteresis in cloud height; solid velocity profiles

Heat transfer and mixing in flow through pinched pipe - Hasabnis, Nilesh S.; Totlani, Kartik A.; Ranade, Vivek V. (Canadian Journal of Chemical Engineering, 2015)
There is an increasing trend of using tubular reactors either with passive or active augmentation methods for process intensification. A new passive method with pinching of pipe' is proposed and investigated for its performance. In the present work, initially, flow in a pinched pipe was studied experimentally and the same was reproduced numerically. The computational model was then used to investigate influences of key geometrical parameters of pinched pipe configuration on pressure drop, heat transfer, and mixing. The simulated results obtained with the pinched pipe were compared with a straight pipe, and with a commonly-used passive augmentation method (twisted tape inserts). The pinched pipe configuration offers better performance and more flexibility in manipulating heat transfer and mixing in intensified devices.
Keywords: computational fluid dynamics (CFD); heat transfer; mixing; pinched pipe; pressure drop

Hydrodynamic cavitation using vortex diode: an efficient approach for elimination of pathogenic bacteria from water - Jain, Pooja; Bhandari, Vinay M.; Balapure, Kshama; Jena, Jyotsnarani; Ranade, Vivek V.; Killedar, Deepak J. (Journal of Environmental Management, 2019)
The present study successfully demonstrates greener methodology of hydrodynamic cavitation using rotational flows for disinfection of water. Disinfection of two model microbial strains-gram-negative (Escherichia colt) and gram-positive (Staphylococcus aureus) using vortex diode was evaluated. The removal efficacy was quantified for two different cavitation reactors. Practically complete elimination of E. coli was achieved (99%) after 1 h of cavitation at a pressure drop of only 0.5 bar. However, elimination of S. aureus using vortex diode was observed to be lower in comparison to the removal of E. coli and only 60% disinfection could be achieved under similar conditions, which can be subsequently enhanced up to 98% by increasing pressure drop. The results were compared with another cavitating device that employs linear flow for cavitation, orifice. The reactor geometry has significant impact on the disinfection process and orifice was found to require significantly higher pressure drop (10 bar) conditions for disinfection and for eliminating grain-positive bacteria with high efficiency. A plausible mechanism for disinfection was proposed to elucidate the role of cavitation in cell destruction leading to death of cells through the rupture of cell wall, oxidative damage and possible DNA denaturation. Also, a cavitation model using per pass disinfection was developed that can provide meaningful physical description of the disinfection process as against the conventional first order reaction rate model. This study would provide meaningful insight into cavitation process based on hydrodynamic cavitation for the destruction of both gram-negative and gram-positive bacteria from various water sources, including industrial wastewaters.
Keywords: Cavitation; Disinfection; kinetics; pollution; Wastewater treatment

Hydrogen solubility in biphasic liquid reaction mixture of cinnamaldehyde hydrogenation: experimental and mathematical modeling study - Khan, Muzammil Y.; Joshi, Sunil S.; Ranade, Vivek V. (Journal of Chemical Sciences, 2022)
The solubility of hydrogen in the biphasic reaction mixture of cinnamaldehyde hydrogenation at 298 to 353 K has been determined in this work experimentally and by using a thermodynamic model. It is evident from many studies that the addition of extra phase, aqueous KOH as the fourth phase, to the three-phase cinnamaldehyde hydrogenation mixture [gas (hydrogen)-liquid (cinnamaldehyde + toluene)-solid (catalyst)] leads to enhancement of cinnamyl alcohol selectivity to a great extent. Determination of hydrogen solubility in this biphasic (organic-aqueous) reaction mixture is crucial to understand the intrinsic reaction kinetics of this reaction. The solubility of hydrogen was experimentally determined using a pressure drop method and reported in terms of Henry's constant. Firstly, hydrogen solubility was determined in pure components viz. toluene, cinnamaldehyde, and water followed by determination of its solubility in the cinnamaldehyde-toluene mixture, aqueous KOH, and eventually, in the reaction mixture containing the two immiscible liquid phases. The effect of changing concentrations in these mixtures and changing phase holdups in the total reaction mixture on hydrogen solubility was studied. Starting from pure components to the reaction mixture, the hydrogen solubility was predicted using a two-step thermodynamic approach involving regular solution theory and the theory of corresponding states. The solubility predictions from this thermodynamic model will be helpful in the accurate estimation of kinetic parameters.
Keywords: biphasic liquid mixture; gas-liquid-liquid-solid [GLLS]; hydrogen solubility; Hydrogenation; thermodynamic model